A Case of Complete Remission from Advanced Gastric Adenocarcinoma with Synchronous Liver Metastasis in Response to EOX Chemotherapy - Zhi-jun Yan; Jia-xin Wang; You-yi Liu; Zhen-hui Li; Li-juan Zhang; Ping Gan; Xiao Han; Li-kun Luan; You-guo Dai (Case Reports in Gastrointestinal Medicine)
Gastric cancer is a malignant tumor with a high degree of malignancy. Multiple liver metastases from gastric cancer (LMGCs) are common. However, the treatment of LMGCs is very difficult. It is rare to achieve complete remission (CR) and long-term survival after treatment. We present the case of a patient with gastric adenocarcinoma and multiple liver metastases who showed CR for more than 33 months after perioperative EOX (epirubicin, oxaliplatin, and capecitabine) combination chemotherapy with radical distal gastrectomy and resection of liver metastases. The patient is still in follow-up without tumor recurrence. These findings suggest that LMGC does not necessarily mean a poor prognosis; preoperative chemotherapy combined with surgery may be a good treatment option for LMGC in selected patients. Further studies are needed to support this treatment approach.